Determinants of the plantation performance for shariah compliant and non- shariah compliant firm / Ikhwan Nafiz Nazaruddin - Nazaruddin, Ikhwan Nafiz (2022)
The purpose of this research is to compare the productivity of plantation firms that follow and do not follow Shariah law. This research focused on the plantation business since it comprises a good mix of shariah compliant and non-shariah finance channels. We used ROA as the dependent variable and Size (Total Asset), Leverage Ratio, and Tangible Asset to Total Asset as independent variables to perform the research (TATA). In assessing the link between dependent and independent variables, Shariah and non-Shariah are compared using panel data from 2017 to 2021. The financial data for Plantation Sector is sourced from Bursa Marketplace's annual report and financial statement. The three independent variables have two significant outcomes: the Leverage Ratio and the Tangible Asset to Total Asset (TATA) with Return on Asset (ROA). Therefore, the success of both sharia-compliant and non-sharia-compliant firms isencouraging.